Nivolumab for relapsed and refractory classical Hodgkin lymphoma: retrospective single center analysis - Magdalena Witkowska; Mikołaj Malicki; Weronika Marcinkowska; Kacper Kościelny; Adrianna Kowalik; Damian Mikulski; Grzegorz Mirocha (Leukemia Research Reports, 2025)
With the introduction of doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) and radiation combined, the prognosis of Hodgkin lymphoma (HL) has significantly improved, with 5-year overall survival of around 90 %. While the lymphoma has become highly curable, the side effects of ABVD treatment are dire and warrant continuous review. Immune checkpoint inhibitors, including nivolumab, have demonstrated high therapeutic efficacy in relapsed and refractory HL patients. Nevertheless, despite much data, the therapy duration and long-term efficacy question remains unresolved. In this retrospective study, in a cohort of 10 patients, we observed a high complete response (CR) rate, while during long-term observation, 5 patients relapsed, and 3 had autoimmune treatment-related complications.